2022
DOI: 10.3390/jintelligence10010004
|View full text |Cite
|
Sign up to set email alerts
|

Parental Stress and Children’s Self-Regulation Problems in Families with Children with Autism Spectrum Disorder (ASD)

Abstract: Background: Increased parental stress is strongly related to the severity of autism spectrum disorder (ASD) symptomatology. Parents’ coping strategies and social support issues add to the complexity of this relationship. Aim: The present study investigated the relationship between self-regulation skills and parenting stress in parents of nonverbal children with ASD. Methods and procedure: The Parenting Stress Index–Short Form (PSI-SF) was administered to 75 families, and self-regulation scores on a Motor Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
2
10
0
2
Order By: Relevance
“…Parenting style was more positively associated with emotion regulation in the male sample, and male students received more emotion regulation exercises from social student-faculty interaction, while female students promote emotion regulation by academic student-faculty interaction. On the one hand, our findings confirm that undergraduate students' emotional development is indeed influenced by both family parenting styles and school interaction environment, which is consistent with international research (Saariaho et al, 2018;Efstratopoulou et al, 2022). On the other hand, our survey based on Chinese undergraduate students revealed some novelty findings comparing to international studies, namely, gender differences in the relationship between parenting styles, student-faculty interaction, and emotion regulation might arise from different gender values in China's unique traditional culture (Zhang, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Parenting style was more positively associated with emotion regulation in the male sample, and male students received more emotion regulation exercises from social student-faculty interaction, while female students promote emotion regulation by academic student-faculty interaction. On the one hand, our findings confirm that undergraduate students' emotional development is indeed influenced by both family parenting styles and school interaction environment, which is consistent with international research (Saariaho et al, 2018;Efstratopoulou et al, 2022). On the other hand, our survey based on Chinese undergraduate students revealed some novelty findings comparing to international studies, namely, gender differences in the relationship between parenting styles, student-faculty interaction, and emotion regulation might arise from different gender values in China's unique traditional culture (Zhang, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Parenting styles play an important role in the development of emotion regulation (Efstratopoulou et al, 2022). From psychological perspective, parenting style refers to the pattern of behavior in raising and educating children, including parenting behavior, attitudes and emotional support (Şiţoiu and Pânişoarȃ, 2022).…”
Section: Parenting Styles and Emotion Regulationmentioning
confidence: 99%
“…Recently, the focus has begun to shift from examining ASD individuals' connections with and experiences of their parents (Ang & Loh, 2019;Cage et al, 2018;Cai et al, 2020;Efstratopoulou et al, 2022;Kutuk et al, 2021;Wang et al, 2020;Yaacob et al, 2021) to exploring the relationships and experiences of ASD individuals with their typically developing siblings. Some past studies that use a quantitative approach (Corsano et al, 2017;Dansby et al, 2018;Hanvey et al, 2022;Lovell and Wetherell, 2016) and qualitative approach (Hanvey et al, 2022;Iannuzzi et al, 2022;Leedham et al, 2020;Thomas et al, 2015;Walton, 2016in Rixon et al, 2021 have observed difficulties in psychosocial adjustment among typically developing siblings of individuals with ASD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most importantly, parental characteristics may be key to the child’s success, as studies have shown improved outcomes in parents with more psychological support [ 83 ], positive emotionality [ 84 ], engagement with the child [ 85 ] and in those that can accept the diagnosis and understand their child’s perspective [ 86 ]. Conversely, parental stress can adversely affect the child’s outcome [ 85 ], including causing them to have poorer self-regulation skills [ 87 ]. Appropriate instruments to measure these important aspects of life in children with ASD are not well developed.…”
Section: Specific Factors To Address In Autism Spectrum Disordermentioning
confidence: 99%
“…Appropriate instruments to measure these important aspects of life in children with ASD are not well developed. While many studies have conducted interviews or developed novel questionnaires, other studies have used the Parental Stress Index [ 87 ] or standardized quality-of-life questionnaires [ 10 , 12 ].…”
Section: Specific Factors To Address In Autism Spectrum Disordermentioning
confidence: 99%